Securing Irrigation in Rainfed Areas : Strategies and Experiences of the West Bengal Accelerated Development of Minor Irrigation Project - World Bank (World Bank, Washington, DC, 2017)
The World Bank supported West Bengal Accelerated Development of Minor Irrigation Project assumes a centre stage position in the current context of bringing water to every farm (Har Khet ko Pani) under the recently launched Pradhan Mantri Krishi Sinchayee Yojana (PMSKY). With an objective to "enhance agricultural production of small and marginal farmers of the project area in West Bengal through development of minor irrigation infrastructure and agriculture support system", the Project was launched in 2012, partnering the Department of Water Resources Investigation and Development, Government of West Bengal. To achieve its outcomes, the Project focuses on strengthening community-based organizations, especially water users' association with a strong focus on gender aspects, irrigation systems development and improvement, agriculture, horticulture and fisheries development.